2010
DOI: 10.1021/jf1016303
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids Suppress the Growth and Induce Apoptosis through Caspase-3-Dependent Pathways in Glioblastoma Multiforme (GBM) 8401 Cells

Abstract: Curcuminoids, natural plant components, have been recently shown to display antioxidant and anti-inflammatory activities. They also produce potent chemo-preventive action against several types of cancer. In the present study, the anti-proliferative and induced apoptosis effects of curcuminoids have been investigated in human brain glioblastoma multiforme (GBM) 8401 cells. Results indicated that curcuminoids have produced an inhibition of cell proliferation in a dose-dependent manner as dosage increased from 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 44 publications
3
38
0
1
Order By: Relevance
“…It is clear that the increased proliferation and decreased cell death (apoptosis) are two major processes that contribute to the progression of tumor cell growth [33]. LDH is a stable cytoplasmic enzyme present in all cells and is rapidly released into the surrounding medium when membrane of cells is damaged [34]. For this reason, LDH assay is widely used as an indicator of irreversible cell death due to cellular membrane damage of various molecules [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the increased proliferation and decreased cell death (apoptosis) are two major processes that contribute to the progression of tumor cell growth [33]. LDH is a stable cytoplasmic enzyme present in all cells and is rapidly released into the surrounding medium when membrane of cells is damaged [34]. For this reason, LDH assay is widely used as an indicator of irreversible cell death due to cellular membrane damage of various molecules [34].…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Previous studies found 49,50 that the inhibitory mechanism of p53 that relied on NF-κB existed in the kidney cancer cells. Quinacrine inhibited NF-κB and activated tumor suppressors of p53 simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, caspase-3, a widely accepted hallmark of programmed cell death, is able to cleave a broad range of cellular substrates and promote activation of DNA endonuclease (23); thus the activation of caspases-3 is a key molecular stage in apoptotic cell death in glioblastoma multiforme. Huang et al (24) demonstrated that curcuminoids can also suppress cell growth and induce apoptosis in GBM 8401 cells through affecting caspase-3-dependent signaling pathways. In the present study, flow cytometry results demonstrated that the number apoptotic cells in the PTTG2 overexpression group were significantly reduced in comparison with the untreated group, while the number of apoptotic cells in the siRNA-PTTG2 interference group were reduced in comparison with the untreated group.…”
Section: D Ementioning
confidence: 99%